2011
DOI: 10.2139/ssrn.1974877
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Residential Segregation and Immigrants’ Perceptions of Discrimination in West Germany

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Nevertheless, our study contributes to current segregation theory and research in several respects. First, extending studies on the consequences of segregation for social mobility and integration, in particular regarding immigrant populations in European societies (e.g., Dill and Jirjahn ), our findings suggest that behavioral discrimination also exists in dyadic social exchange relations between individuals from different neighborhoods. In addition to evidence regarding generalized trust (Putnam ; Uslaner , ), this finding is important because it refers to trust in specific social exchanges in which both players can be better off when they cooperate.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Nevertheless, our study contributes to current segregation theory and research in several respects. First, extending studies on the consequences of segregation for social mobility and integration, in particular regarding immigrant populations in European societies (e.g., Dill and Jirjahn ), our findings suggest that behavioral discrimination also exists in dyadic social exchange relations between individuals from different neighborhoods. In addition to evidence regarding generalized trust (Putnam ; Uslaner , ), this finding is important because it refers to trust in specific social exchanges in which both players can be better off when they cooperate.…”
Section: Discussionsupporting
confidence: 70%
“…In general, existing research suggests that the integration of immigrants differs across countries and groups, although immigrants from other European countries are substantially less isolated than those from the Middle East, Asia, and Africa (Glikman and Semyonov ). For example, studies have shown that immigrants in segregated neighborhoods report ethnic discrimination more frequently (Dill and Jirjahn ), that ethnic diversity can negatively affect collective efficacy (Kleinhans and Bolt ), and that the size of some ethnic neighborhood minorities is linked to less positive attitudes toward those minorities (Havekes et al. ).…”
Section: Residential Segregation: Causes and Consequencesmentioning
confidence: 99%